Anti-aging self-adhesion waterproof roll cementing material, waterproof roll and preparation method
By using the aging-resistant self-adhesive waterproof coil cement prepared by using raw materials such as Chongjiao 70# asphalt, homemade high-grade waterproof asphalt, etc., the existing self-adhesive waterproof coil has solved the problems of complex production process, environmental pollution and poor anti-aging performance, and achieved efficient and environmentally friendly waterproof performance and long life.
Patent Information
- Application Number
- CN202311432069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing self-adhesive waterproof coils need to be added to softened oil and waste glue powder during the production process, resulting in complex preparation process, environmental pollution, poor anti-aging performance and short service life.
The aging-resistant self-adhesive waterproof asphalt, homemade high-grade waterproof asphalt, SBS, SIS, tackifying resin, waste glue powder and sesapite powder are used as raw materials. Through high-temperature mixing and high-speed shearing and other processes, aging-resistant self-adhesive waterproof coil cement is prepared.
The cement has high strength, good environmental protection, good water resistance, high and low temperature performance and anti-aging properties, extending the service life of self-adhesive waterproof coils, simplifying the preparation process, and reducing production costs.
Smart Images

Figure BDA0004523941440000091 
Figure BDA0004523941440000092 
Figure BDA0004523941440000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building waterproof engineering, and specifically relates to an aging-resistant self-adhesive waterproof coiled material binder and a self-adhesive waterproof coiled material, and further discloses a preparation method thereof. Background Art
[0002] With the development of economy and the progress of the times, the requirements for the performance of building materials are getting higher and higher. The original building materials can no longer meet the needs of the development of the times. Many buildings have reduced their service life due to water erosion. As people's requirements for the service life of buildings are getting higher and higher, people pay more and more attention to the quality of waterproof materials.
[0003] At present, domestic elastomer (SBS) modified asphalt waterproofing membrane is still the mainstream product, especially when used on exposed roofs, because its superior high temperature resistance is difficult to replace by other materials. However, elastomer (SBS) modified asphalt waterproofing membrane needs to be hot-melt during construction, and there is a great fire hazard when the blowtorch is baked. In addition, the burning of the surface PE film during the baking process and the decomposition of some modified asphalt binders due to heating will also produce some dioxins, hydrocarbons and other harmful substances, causing serious pollution to the environment.
[0004] Based on the above problems, researchers have developed a variety of self-adhesive waterproofing membranes with different performances. Self-adhesive membranes are a new type of waterproof material that can be constructed at room temperature and does not require hot melt construction, and are widely favored by the market. The existing self-adhesive membrane waterproofing membrane binder needs to add softening oil during the production process. Not only is the preparation process more complicated, but the volatile organic matter contained in the softening oil is easy to volatilize during the production process, which not only pollutes the environment and affects the anti-aging performance of the waterproof material, but also reduces the life of the waterproof membrane, causing unnecessary economic losses. In the production process of self-adhesive waterproof membranes, waste rubber powder is usually added. Although waste rubber powder modified asphalt can consume a large amount of waste tires, waste rubber will release a large amount of harmful fumes during the high-temperature production process, which not only endangers human health, but also brings great challenges to the environment. More importantly, when traditional self-adhesive waterproof membranes are exposed for a long time, the mineral particles on the surface are easy to fall off and age, resulting in a large number of cracks or cracks on the surface of the waterproof layer, affecting the waterproof function and the service life of the material. Summary of the invention
[0005] To this end, the technical problem to be solved by the present invention is to provide an aging-resistant self-adhesive waterproof membrane binder, which not only has high strength and good environmental protection, but also has good water resistance, high and low temperature performance and aging resistance;
[0006] The second technical problem to be solved by the present invention is to provide an aging-resistant self-adhesive waterproof roll material, which has better anti-aging performance and longer service life;
[0007] The third technical problem to be solved by the present invention is to provide a method for preparing an aging-resistant self-adhesive waterproof membrane binder and a self-adhesive waterproof membrane.
[0008] In order to solve the above technical problems, the present invention discloses an aging-resistant self-adhesive waterproof membrane binder, wherein the binder comprises the following raw materials in parts by weight: 30-40 parts by weight of 70# asphalt, 50-60 parts by weight of high-grade waterproof asphalt, 8-12 parts by weight of SBS, 2-5 parts by weight of SIS (styrene-isoprene-styrene block copolymer), 5-8 parts by weight of tackifying resin, 8-10 parts by weight of waste rubber powder, and 10-20 parts by weight of sepiolite powder;
[0009] The high-grade waterproof asphalt includes the following raw materials: base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler, adsorbent;
[0010] Preferably, the mass ratio of the base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler and adsorbent is 70-80:6-10:10-18:0.1-0.25:1-3:0.03-0.05.
[0011] Specifically, the aging-resistant self-adhesive waterproof membrane binder:
[0012] The SBS is a linear SBS with a melt index of 0.03-0.10 g / min; and / or,
[0013] The SIS is a linear SIS with a melt index of 0.9-1.6 g / min; and / or,
[0014] The tackifying resin comprises a mixture of coumarone resin, terpene resin and C5 resin; preferably, the mass ratio of coumarone resin, terpene resin and C5 resin is 1-3:1-3:1-3; and / or,
[0015] The particle size of the waste rubber powder is 60-80 mesh; and / or,
[0016] The particle size of the sepiolite powder is 80-100 meshes.
[0017] Specifically, in the aging-resistant self-adhesive waterproof membrane binder, in the high-grade waterproof asphalt, the furfural extracted oil includes one or a mixture of two of furfural extracted oil with three-line reduction and furfural extracted oil with four-line reduction;
[0018] Preferably, the aromatic content in the furfural extracted oil is ≥40%.
[0019] Specifically, in the aging-resistant self-adhesive waterproof coiled material binder, the high-grade waterproof asphalt, the adsorbent includes bamboo wood nanofiber aerogel;
[0020] Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions for immersion, and the step of pressurizing and heating the bamboo wood nanofibers;
[0021] Preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers for immersion for 20-30 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution for immersion for 20-30 hours;
[0022] More preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers and impregnating them for 24 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution to impregnate them for 24 hours;
[0023] Preferably, the pressure and heat treatment step is performed for 6-10 hours, and preferably for 8 hours.
[0024] Specifically, in the aging-resistant self-adhesive waterproof membrane binder, the high-grade waterproof asphalt, the filler includes activated palygorskite;
[0025] Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; the preferred treatment temperature is 60° C.;
[0026] Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%;
[0027] Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; the preferred mass ratio is 1:3 g / mL;
[0028] Preferably, the treatment time is 40-80 min; preferably, the treatment time is 60 min;
[0029] Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
[0030] Specifically, the aging-resistant self-adhesive waterproof membrane binder and the high-grade waterproof asphalt include:
[0031] The base asphalt includes heavy cross-linking 70# asphalt; and / or,
[0032] The aromatic content of the catalytic cracking slurry is 40%-48%; and / or,
[0033] The converting agent includes silicotungstic acid.
[0034] The present invention also discloses a method for preparing the aging-resistant self-adhesive waterproof coiled material binder, comprising the steps of mixing selected amounts of the 70# asphalt, high-grade waterproof asphalt, SBS, SIS, tackifying resin, waste rubber powder and sepiolite powder;
[0035] Preferably, the temperature of the mixing step is 170-180°C;
[0036] Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3000-3500 r / min for 1-1.5 h during the mixing process;
[0037] Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3200 r / min for 1.2 h during the mixing process.
[0038] Specifically, the method for preparing the aging-resistant self-adhesive waterproof membrane binder further comprises the step of preparing the high-grade waterproof asphalt, namely, the step of mixing selected amounts of the base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, absorbent and filler;
[0039] Preferably, the temperature of the mixing step is 120°C-130°C, preferably the mixing temperature is 125°C.
[0040] Specifically, the method for preparing the anti-aging waterproof asphalt comprises the following steps:
[0041] (1) heating a selected amount of the base asphalt to 120° C.-130° C.;
[0042] (2) continuing to add the selected amount of the catalytic oil slurry and furfural extracted oil, and performing high-speed shearing at a speed of 1000-1500 r / min for 30-40 min; preferably, performing high-speed shearing at a speed of 1200 r / min for 35 min;
[0043] (3) continuing to add the selected amount of the conversion agent and absorbent, and continuing shearing for 20-40 minutes, and then continuing shearing under ultrasonic conditions for 0.5-1 hour;
[0044] (4) Continue to add the selected amount of the filler and continue shearing for 20-40 minutes.
[0045] Specifically, in the method for preparing the anti-aging waterproof asphalt, in the step (3), the power of the ultrasonic step is 4-8W, preferably 6W, and the ultrasonic time is 0.5-1h.
[0046] The present invention also discloses an aging-resistant self-adhesive waterproof coiled material, comprising a polyester base, a bonding layer coated on the surface of the polyester base, and a protective film covering the surface;
[0047] The bonding layer is formed by the ageing-resistant self-adhesive waterproof membrane bonding material.
[0048] The invention also discloses a method for preparing the ageing-resistant self-adhesive waterproof coiled material, comprising the steps of coating the ageing-resistant self-adhesive waterproof coiled material binder on the surface of a selected polyester substrate, and cooling the coating.
[0049] The aging-resistant self-adhesive waterproof coiled material binder of the present invention adopts heavy cross-linked 70#, high-grade waterproof asphalt, SBS, SIS, tackifying resin, waste rubber powder and sepiolite powder as raw materials, and the various components cooperate with each other, especially adopting homemade aging-resistant high-grade waterproof asphalt as raw material, and the waterproof coiled material binder can be produced without adding softening oil, which can not only improve the anti-aging and waterproof performance of the material, but also effectively prolong the service life of the material, thereby overcoming the disadvantages of the complicated process of the traditional preparation method.
[0050] The ageing-resistant self-adhesive waterproof coiled material binder of the present invention has a special structure of sepiolite powder, which can reduce the surface temperature of the coiled material and extend its service life under high temperature conditions; and the use of waste rubber powder as raw material not only makes rational use of waste resources and greatly reduces production costs, but also increases the added value of products.
[0051] The aging-resistant self-adhesive waterproof coiled material binder of the present invention adopts self-made aging-resistant high-grade waterproof asphalt as raw material, and the selected catalytic cracking oil slurry and furfural extracted oil contain more saturated components and aromatic components, which are beneficial to the swelling of SBS and SIS in the process of preparing the coiled material; and silicotungstic acid is added as a conversion agent in the preparation process. The presence of silicotungstic acid converts the aromatic components into high molecular weight substances in the heating process, reduces the volatilization of harmful substances, and protects the environment; bamboo wood nanofiber aerogel is used as an adsorbent, and the aerogel reacts in the preparation process to make it have a special fiber frame structure, which can adsorb organic light components volatilized in the preparation process, reduces the volatilization of light components, protects the environment, improves the anti-aging performance of the waterproof coiled material, and improves the low temperature resistance of the coiled material. Performance: As a natural mineral microfiber, the palygorskite in waterproof asphalt has a large number of fibers forming a reinforced network, which is entangled with the spatial network of SBS and SIS, reducing the volatilization of saturated components with lower molecular weight in the asphalt and improving the anti-aging performance of the asphalt. After acidification, the palygorskite can coat the light components, reducing the volatilization of the light components, protecting the environment and improving the low-temperature performance of the asphalt. After acidification, the palygorskite can coat the light components, reducing the volatilization of the light components, protecting the environment and improving the low-temperature performance of the asphalt. In particular, palygorskite and sepiolite have a large specific surface area and a special layered chain structure, which makes them have a large specific surface contact area with asphalt, improving the high and low temperature performance of the roll material and enhancing the anti-aging performance.
[0052] The aging-resistant self-adhesive waterproof membrane binder and the self-adhesive waterproof membrane of the present invention are not only simple to manufacture, but also have excellent high and low temperature performance and anti-aging performance and better environmental protection performance. They shorten the process flow for waterproof membrane production enterprises and have better economic feasibility. They are suitable for waterproofing and anti-seepage of industrial and civil building roofs, walls, kitchens and bathrooms, basements, swimming pools, as well as roads, bridges, subways, reservoirs and other projects, and are also suitable for anti-corrosion protection of metal containers and pipelines. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.
[0054] In the following preparation example of the present invention, the filler is activated palygorskite, and the preparation method of the activated palygorskite comprises: mixing palygorskite with 2% hydrochloric acid by mass fraction at a solid-liquid ratio of 1:3, treating at 60°C for 60 minutes, washing with water, and drying.
[0055] In the following preparation example of the present invention, the adsorbent is bamboo wood nanofiber aerogel, and the preparation method of the bamboo wood nanofiber aerogel comprises: soaking the bamboo wood cellulose nanofiber in water for 24 hours, then taking out the bamboo wood nanofiber and continuing to soak it in an ethanol solution for 24 hours, and after taking it out, heating the nanofiber in a pressurized oven for 8 hours to obtain the desired bamboo wood nanofiber aerogel.
[0056] In the following preparation examples, comparative preparation examples, embodiments and comparative examples of the present invention, the properties and parameters of the same raw material components are the same.
[0057] Preparation Example 1
[0058] Heat 70 parts of heavy cross-linked 70# asphalt to 125°C, add 6 parts of catalytic oil slurry and 10 parts of furfural extracted oil, and mix them. High-speed shearing is performed at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.1 parts of silicotungstic acid and 0.03 parts of bamboo wood nanofiber aerogel, and continue to shear for 30 minutes, then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 1 part of activated palygorskite and continue to shear for 30 minutes.
[0059] Preparation Example 2
[0060] Heat 75 parts of heavy cross-linked 70# asphalt to 125°C, add 8 parts of catalytic oil slurry and 14 parts of furfural extraction oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.15 parts of silicotungstic acid and 0.04 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 2 parts of activated palygorskite and continue to shear for 30 minutes.
[0061] Preparation Example 3
[0062] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5h, continue to maintain the temperature, add 3 parts of activated palygorskite and continue to shear for 30 minutes.
[0063] Comparative Preparation Example 1
[0064] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them. Shear them at a high speed of 1200r / min for 35 minutes. Continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and shear for 30 minutes, then continue to shear for 0.5h under ultrasonic conditions (power 6W), and finally add 3 parts of activated palygorskite at this temperature and continue to shear for 30 minutes.
[0065] Comparative Preparation Example 2
[0066] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them. Shear them at a high speed of 1200r / min for 35 minutes. Continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, and then continue to shear for 0.5h under ultrasonic conditions (6W).
[0067] Comparative Preparation Example 3
[0068] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them. Shear them at a high speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5h under ultrasonic (6W) conditions, and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0069] Comparative Preparation Example 4
[0070] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, high-speed shear at 1200r / min for 35min, and then continue shearing for 0.5h under ultrasonic (6W) conditions to obtain the product.
[0071] Comparative Preparation Example 5
[0072] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them. High-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0073] Comparative Preparation Example 6
[0074] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them. Shear them at a high speed of 1200r / min for 35 minutes. Continue to maintain the temperature at 125°C, add 0.25 parts of phosphomolybdic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5h under ultrasonic conditions, and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0075] The properties of the high-grade waterproof asphalt prepared in the above-mentioned Preparation Examples 1-3 were respectively measured and shown in Table 1 below.
[0076] Table 1 Performance of high-grade waterproof asphalt in Preparation Examples 1-3
[0077]
[0078] The properties of the high-grade waterproof asphalt prepared in the above comparative preparation examples 1-6 were respectively measured and shown in Table 2 below.
[0079] Table 2 Comparative properties of high-grade waterproof asphalt in preparation examples 1-6
[0080]
[0081] It can be seen from the data in Tables 1 and 2 above that the high-grade waterproof asphalt material prepared using the raw material system of the present invention has good application performance in all aspects, and the softening point increment of the prepared high-grade waterproof asphalt before and after aging is small, and the evaporation loss is small, indicating that the high-grade waterproof asphalt prepared using the present invention has good anti-aging performance.
[0082] In the following examples of the present invention, the required binder is prepared based on the high-grade waterproof asphalt prepared in the aforementioned Preparation Example 3 as raw material.
[0083] In the following examples and comparative examples of the present invention, the tackifying resin includes a mixture of coumarone resin, terpene resin and C5 resin; the mass ratio of the coumarone resin, terpene resin and C5 resin is 1:1:1.
[0084] Example 1
[0085] First, heat 30 parts of 70# asphalt and 50 parts of homemade high-grade waterproof asphalt (Preparation Example 3) to 175°C, add 8 parts of SBS and 2 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then add 5 parts of tackifying resin and shear at this temperature and speed for 0.5 hours. Finally, add 8 parts of waste rubber powder and 10 parts of sepiolite powder, and continue shearing at this temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0086] The aging-resistant self-adhesive waterproof membrane described in this embodiment is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0087] Example 2
[0088] First, heat 35 parts of 70# asphalt and 55 parts of homemade high-grade waterproof asphalt to 175°C, add 10 parts of SBS and 3 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then add 7 parts of tackifying resin and shear at the temperature and speed for 0.5 hours. Finally, add 9 parts of waste rubber powder and 15 parts of sepiolite powder, and continue shearing at the temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0089] The aging-resistant self-adhesive waterproof membrane described in this embodiment is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0090] Example 3
[0091] First, heat 40 parts of 70# asphalt and 60 parts of homemade high-grade waterproof asphalt to 175°C, add 12 parts of SBS and 5 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then add 8 parts of tackifying resin and shear at the temperature and speed for 0.5 hours. Finally, add 10 parts of waste rubber powder and 20 parts of sepiolite powder, and continue shearing at the temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0092] The aging-resistant self-adhesive waterproof membrane described in this embodiment is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0093] Comparative Example 1
[0094] First, heat 30 parts of 70# asphalt and 50 parts of commercially available high-grade waterproof asphalt (F400 high-grade liquid asphalt) to 175°C, add 8 parts of SBS and 2 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then add 5 parts of tackifying resin and shear at the temperature and speed for 0.5 hours. Finally, add 8 parts of waste rubber powder and 10 parts of sepiolite powder, and continue shearing at the temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0095] The aging-resistant self-adhesive waterproof membrane described in this comparative example is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0096] Comparative Example 2
[0097] First, heat 30 parts of 70# asphalt and 50 parts of homemade high-grade waterproof asphalt to 175°C, add 8 parts of SBS and 2 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then add 5 parts of tackifying resin and shear at the temperature and speed for 0.5 hours. Finally, add 8 parts of waste rubber powder and 10 parts of talcum powder and continue to shear at the temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0098] The aging-resistant self-adhesive waterproof membrane described in this comparative example is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0099] Comparative Example 3
[0100] First, heat 30 parts of 70# asphalt and 50 parts of commercially available high-grade waterproof asphalt to 175°C, add 8 parts of SBS and 2 parts of SIS, and shear at a speed of 3200r / min for 1.2 hours. Then, add 5 parts of tackifying resin and shear at the same temperature and speed for 0.5 hours. Finally, add 8 parts of waste rubber powder and 10 parts of talcum powder and continue shearing at the same temperature and speed for 1 hour to obtain the self-adhesive waterproof membrane binder.
[0101] The aging-resistant self-adhesive waterproof membrane described in this comparative example is prepared by evenly covering the self-adhesive waterproof membrane binder prepared above on a polyester base, and then laminating and cooling.
[0102] The properties of the waterproof membranes prepared in the above Examples 1-3 and Comparative Examples 1-3 were measured respectively.
[0103] Table 3 is Japan's six-level odor intensity classification table. Referring to Japan's six-level odor intensity classification method, the waterproof membranes made of asphalt binders of Examples 1-3 and Comparative Examples 1-3 were evaluated for various properties. The evaluation results are shown in Table 4.
[0104] Table 3 Japanese odor intensity grades
[0105] strength index 0 Odorless 1 Barely able to detect smell 2 The smell is very weak but the properties can be distinguished 3 It is easy to sense the smell 4 Strong smell 5 Unbearable strong smell
[0106] Table 4 Performance of waterproof membrane in Examples and Comparative Examples
[0107]
[0108] It can be seen from the data in Table 4 that the waterproof coiled material prepared by the raw material system of the present invention not only has good waterproof performance, better environmental performance, but also has excellent low-temperature flexibility and heat resistance. When the coiled material prepared by the formula is exposed to direct sunlight for 1 hour at an ambient temperature of 25°C, the temperature rise on the surface of the coiled material is small, indicating that the coiled material can reduce the surface temperature of the coiled material under high temperature conditions, reduce aging, and improve aging resistance.
[0109] The coiled material prepared by the present invention can be applied to waterproofing and anti-seepage of industrial and civil building roofs, walls, kitchens and bathrooms, basements, swimming pools, as well as roads, bridges, subways, reservoirs and other projects, and can also be applied to anti-corrosion protection of metal containers and pipelines.
[0110] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. An aging-resistant self-adhesive waterproof membrane binder, characterized in that: The binder comprises the following raw materials in parts by weight: 30-40 parts by weight of 70# asphalt, 50-60 parts by weight of high-grade waterproof asphalt, 8-12 parts by weight of SBS, 2-5 parts by weight of SIS (styrene-isoprene-styrene block copolymer), 5-8 parts by weight of tackifying resin, 8-10 parts by weight of waste rubber powder, and 10-20 parts by weight of sepiolite powder; The high-grade waterproof asphalt includes the following raw materials: base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler, adsorbent; Preferably, the mass ratio of the base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler and adsorbent is 70-80:6-10:10-18:0.1-0.25:1-3:0.03-0.
05.
2. The ageing-resistant self-adhesive waterproof membrane binder according to claim 1 is characterized by: The SBS is a linear SBS with a melt index of 0.03-0.10 g / min; and / or, The SIS is a linear SIS with a melt index of 0.9-1.6 g / min; and / or, The tackifying resin comprises a mixture of coumarone resin, terpene resin and C5 resin; preferably, the mass ratio of coumarone resin, terpene resin and C5 resin is 1-3:1-3:1-3; and / or, The particle size of the waste rubber powder is 60-80 mesh; and / or, The particle size of the sepiolite powder is 80-100 meshes.
3. The aging-resistant self-adhesive waterproof membrane binder according to claim 1 or 2, characterized in that: In the high-grade waterproof asphalt, the furfural extracted oil includes one or a mixture of two of furfural extracted oil with three-line reduction and furfural extracted oil with four-line reduction; Preferably, the aromatic content in the furfural extracted oil is ≥40%.
4. The aging-resistant self-adhesive waterproof membrane binder according to any one of claims 1 to 3, characterized in that: In the high-grade waterproof asphalt, the adsorbent includes bamboo wood nanofiber aerogel; Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions for immersion, and the step of pressurizing and heating the bamboo wood nanofibers; Preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers for immersion for 20-30 hours, and then taking out the bamboo wood cellulose nanofibers and continuing to add ethanol solution for immersion for 20-30 hours; Preferably, the pressure and heat treatment step is performed for 6-10 hours.
5. The aging-resistant self-adhesive waterproof membrane binder according to any one of claims 1 to 4, characterized in that: In the high-grade waterproof asphalt, the filler includes activated palygorskite; Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%; Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; Preferably, the treatment time is 40-80 min; Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
6. The ageing-resistant self-adhesive waterproof membrane binder according to any one of claims 1 to 5, characterized in that: The high-grade waterproof asphalt: The base asphalt includes heavy cross-linking 70# asphalt; and / or, The aromatic content of the catalytic cracking slurry is 40%-48%; and / or, The converting agent includes silicotungstic acid.
7. A method for preparing the aging-resistant self-adhesive waterproof membrane binder according to any one of claims 1 to 6, characterized in that: The method comprises the steps of mixing selected amounts of the 70# asphalt, high-grade waterproof asphalt, SBS, SIS, tackifying resin, waste rubber powder and sepiolite powder; Preferably, the temperature of the mixing step is 170-180°C; Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3000-3500 r / min for 1-1.5 h during the mixing process.
8. The method for preparing the aging-resistant self-adhesive waterproof membrane binder according to claim 7, characterized in that: The method further comprises the step of preparing the high-grade waterproof asphalt, namely, the step of mixing selected amounts of the base asphalt, catalytic slurry, furfural extracted oil, conversion agent, absorbent and filler; Preferably, the temperature of the mixing step is 120°C-130°C.
9. An aging-resistant self-adhesive waterproof coiled material, characterized in that: It comprises a polyester tire, a bonding layer coated on the surface of the polyester tire, and a protective film covering the surface; The bonding layer is formed by the ageing-resistant self-adhesive waterproof membrane bonding material according to any one of claims 1 to 6.
10. A method for preparing the aging-resistant self-adhesive waterproof coiled material according to claim 9, characterized in that: The method comprises the steps of coating the anti-aging self-adhesive waterproof coiled material binder on the surface of a selected polyester tire and cooling the film.